Iron Isotopic Composition of Biological Standards Relevant to Medical and Biological Applications - Kubik, Edith; Moynier, Frédéric; Paquet, Marine; Siebert, Julien (Frontiers in Medicine, 2021)
Iron isotopes are fractionated by multiple biological processes, which offers a novel opportunity to study iron homeostasis. The determination of Fe isotope composition of biological samples necessitates certified biological reference materials of known Fe isotopic signature in order to properly assess external reproducibility and data quality between laboratories. We report the most comprehensive study on the Fe isotopic composition for widely available international biological reference materials. They consist of different terrestrial and marine animal organs (bovine, porcine, tuna, and mussel) as well as apple leaves and human hair (ERC-CE464, NIST1515, ERM-DB001, ERMBB186, ERM-BB184, ERM-CE196, BCR668, ERM-BB185, ERM-BB124). Previously measured Fe isotopic compositions were available for only two of these reference materials (ERC-CE464 tuna fish and ERMBB186 pig kidney) and these literature data are in excellent agreement with our data. The Fe isotopic ratios are reported as the permil deviation of the 56Fe/54Fe ratio from the IRMM-014 standard. All reference materials present d56Fe ranging from -2.27 to -0.35 ‰. Combined with existing data, our results suggest that animal models could provide useful analogues of the human body regarding the metabolic pathways affecting Fe isotopes, with many potential applications to medicine.